2020
DOI: 10.1056/nejmoa2022190
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Renal Outcomes with Empagliflozin in Heart Failure

Abstract: BACKGROUND Sodium-glucose cotransporter 2 (SGLT2) inhibitors reduce the risk of hospitalization for heart failure in patients regardless of the presence or absence of diabetes. More evidence is needed regarding the effects of these drugs in patients across the broad spectrum of heart failure, including those with a markedly reduced ejection fraction. METHODS In this double-blind trial, we randomly assigned 3730 patients with class II, III, or IV heart failure and an ejection fraction of 40% or less to receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

98
3,163
11
194

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 3,516 publications
(3,466 citation statements)
references
References 10 publications
98
3,163
11
194
Order By: Relevance
“…Those with HF at baseline drived the most benefit [37], fueling speculations regarding the mechanism of cardioprotection mediated by SGLT2 inhibitors. However, in the DAPA-HF and the EMPEROR-Reduced trials-two dedicated HF trialsthe SGLT2 inhibitors dapagliflozin and empagliflozin reduced hospitalization for HF similarly in non-diabetic and diabetic HFrEF patients [5,6]. These data suggest that SGLT2 inhibitors have direct cardioprotective effects in HF, which are independent of the presence of T2DM [38,39].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Those with HF at baseline drived the most benefit [37], fueling speculations regarding the mechanism of cardioprotection mediated by SGLT2 inhibitors. However, in the DAPA-HF and the EMPEROR-Reduced trials-two dedicated HF trialsthe SGLT2 inhibitors dapagliflozin and empagliflozin reduced hospitalization for HF similarly in non-diabetic and diabetic HFrEF patients [5,6]. These data suggest that SGLT2 inhibitors have direct cardioprotective effects in HF, which are independent of the presence of T2DM [38,39].…”
Section: Discussionmentioning
confidence: 96%
“…Selective sodium-glucose cotransporter 2 (SGLT2) inhibitors are novel oral antidiabetic agents that block SGLT2 in the proximal convoluted tubule of the kidney, resulting in increased glucose excretion. Recent cardiovascular outcome trials in patients with type 2 diabetes mellitus (T2DM) [1][2][3], and dedicated heart failure (HF) trials in patients with HF and reduced ejection fraction (HFrEF) with or without T2DM [4][5][6] have demonstrated a consistently significant reduction in hospitalization for HF with SGLT2 inhibitor treatment versus placebo. Therefore, it has been postulated that SGLT2 inhibition in the kidney does not serve as full explanation for the marked clinical benefits associated with SGLT2 inhibitor treatment [7][8][9][10][11], suggesting direct cardiovascular mechanisms, which are currently incompletely understood given that SGLT2 is not expressed in the normal or diseased heart [9,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the antidiabetic drug empagliflozin on top of optimized medical therapy reduced the composite primary endpoint of CV death and hospitalization in patients with HF and reduced ejection fraction (HFrEF), with the great majority of them presenting with a left ventricle ejection fraction (LVEF) of ≤ 30%. In addition, empagliflozin showed positive effects on reducing the progression of kidney disease [23]. A meta-analysis of EMPEROR-Reduced and DAPA-HF trials confirmed these findings [26].…”
mentioning
confidence: 88%
“…In this commentary, we summarized the most important trials presented during the 2020 Virtual ESC Congress (Table 1) which we predict will improve our everyday clinical practice [12][13][14][15][16][17][18][19][20][21][22][23][24]. The EMPEROR-Reduced (EMPagliflozin outcomE tRial in Patients With chrOnic heaRt Failure With Reduced Ejection Fraction) trial [23] further strengthened the positive findings observed in the DAPA-HF (Study to Evaluate the Effect of Dapagliflozin on the Incidence of Worsening Heart Failure or Cardiovascular Death in Patients With Chronic Heart Failure) trial [25]. In this study, the antidiabetic drug empagliflozin on top of optimized medical therapy reduced the composite primary endpoint of CV death and hospitalization in patients with HF and reduced ejection fraction (HFrEF), with the great majority of them presenting with a left ventricle ejection fraction (LVEF) of ≤ 30%.…”
mentioning
confidence: 99%
“…8 More recently, the Empagliflozin Outcome Trial in hospitalisation for HF, but failed to demonstrate benefit in terms of mortality. 9 This article aims to discuss the evidence supporting the use of dapagliflozin and empagliflozin in patients with HFrEF with and without T2D and the optimal place for SGLT2 inhibitors in HF therapy.…”
Section: Treatmentmentioning
confidence: 99%